The effect of a physical therapy programme on the condition of upper limb muscles in patients with rheumatoid arthritis - Grygus, Igor; Nogas, Anzhela (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. Rheumatoid arthritis is a chronic progressive systemic disease of the connective tissue affecting the joints, mainly small, of the erosive-destructive polyarthritis type, and frequent systemic inflammatory damage to internal organs. The purpose of the research is to evaluate the effectiveness of physical therapy on the muscles of upper limbs in patients with rheumatoid arthritis by the dynamics of muscle strength and strength index. Material and methods. To determine the strength of the muscles of the affected upper limbs were used dynamometry, calculated strength index as a percentage to assess the functional ability of the affected limb. All patients were divided into control (n=92) and main (n=96) groups, taking into account the functional insufficiency of the joints. Results. After 6 months of physical therapy, muscle strength indicators in the main group of patients with 1st degree of functional joints insufficiency (FJI) in the affected right limb increased by 3.1 kg, in the left by 3 kg; with 2nd degree FJI – in the right limb by 4.2 kg, in the left – by 3.7 kg, significantly exceeded the same indicators in patients of the control group (р<0.05). Similarly, there was an increase in the strength index in the patients of the main group. Conclusion. Physical therapy technology has been developed and implemented effectively influenced the increase in muscle strength and strength index of affected upper limbs of the main group of patients with rheumatoid arthritis.
The research was carried out in compliance with the main provisions of the “Rules of Ethical Principles of Conducting Scientific Medical Research with Human Participation”, approved by the Declaration of Helsinki (1964-2013), ICH GCP (1996), EU Directive No. 609 (from November 24, 1986) orders of the Ministry of Health of Ukraine No. 690 of 09/23/2009, No. 944 of 12/14/2009, No. 616 of 08/03/2012.
Keywords: dynamometry; muscles strength; physical therapy; rheumatoid arthritis; strength index